DDTC-Cu(I) inhibits human osteosarcoma cells growth by repressing MET/PI3K/AKT signaling pathway - Ruhao Zhou; Lei Yan; Kun Zhang; Song Chen; Yang Yu; Xiaochun Wei; Yongchun Pan; Chaojian Xu; Xiaojuan Sun; Zhi Lv; Pengcui Li; Xiaochen Qiao; et al. (Scientific Reports)
Abstract Osteosarcoma (OS) is a frequently occurring bone malignancy with increased metastatic properties, causing deaths in large numbers around the world. Disulfiram (DSF) is clinically utilized to treat alcohol dependency and has been indicated to bind Cu(I) in-vivo to form DDTC-Cu(I), which has been confirmed for its antitumor effects. This investigation aimed to elucidate the efficacy of DDTC-Cu(I) on OS cell apoptosis, migration, growth, invasion, and underlying mechanisms. The in-vitro investigations were performed on U2OS, SaOS2, and MG-63 OS cell lines and included CCK-8, colony formation, RTCA, transwell invasion, flow cytometry, wound healing, and RNA seq assays. DDTC-Cu(I) was inoculated dose-dependent, increased apoptosis, and suppressed cells’ ability to proliferate, migrate, and invade via the MET and PI3K/AKT signaling pathways. Additionally, MET’s overexpression partially reversed the anti-OS and PI3K/AKT signaling pathways suppression effect of DDTC-Cu(I). Furthermore, the SaOS2 xenograft mice model was utilized to confirm the in-vivo anti-OS efficacy of DDTC-Cu(I) by MET protein inhibition. The histological research revealed that DDTC-Cu(I) had no adverse influence on the liver, heart, lungs, and kidneys. Overall, the data of this investigation suggested that DDTC-Cu(I) could serve as an efficient agent against OS development.